Bio-Sensor Based on Trapped Mode All-Dielectric Metasurface Coated with Graphene Layer to Enhance Sensitivity - Xuesong Deng; Ming Fang; Xingang Ren; Zhixiang Huang; Xianliang Wu; Jiaming Shi (IEEE Photonics Journal, 2021)
All-dielectric metasurfaces have been widely used in nanophotonics because of their properties, such as negligible Ohmic loss, stable properties, and flexible fabrication techniques. We propose an all-dielectric metasurface consisting of subwavelength particles, which supports a “trapped” mode after the introduction of adequate symmetry-breaking in the silicon meta-atoms. Coating the metasurface with monolayer graphene enables the adsorption of nucleic acids such as DNA and RNA. We compare the resonant states in the transmission spectrum and find that the proposed metasurface is ultra-sensitive to the surrounding environment and exhibits excellent biosensing performance. Our conclusions indicate that all-dielectric metasurfaces can be a promising platform to realize ultra-sensitive bio-sensors.